An empirical investigation of a theoretical model for mathematical creativity. (24th March 2016) - Haavold, Per Øystein
Abstract: In this exploratory study, a theoretical model proposed by Sriraman (2005) consisting of five theoretical principles for optimizing creativity in a K–12 setting was investigated empirically. This was accomplished in two steps. In the first study, the five principles were operationalized by generating a questionnaire consisting of 45 items intended to capture the dimension of each principle. An exploratory maximum‐likelihood factor analysis indicated a relatively robust five factor structure that corresponded with the theoretical model. In the second study, the five factor model was validated using a confirmatory factor analysis. The model was then investigated using a two‐level linear mixed model with a random intercept. The results revealed that motivation and mathematical achievement were significant predictors of mathematical creativity.